Shared decision-making during childbirth in maternity units: the VIP mixed-methods study - Ellen Annandale; Helen Baston; Siân Beynon-Jones; Lyn Brierley-Jones; Alison Brodrick; Paul Chappell; Josephine Green; Clare Jackson; Victoria Land; Tomasina Stacey (NIHR Journals Library, 2022)
Background: NHS policy emphasises shared decision-making during labour and birth. There is, however, limited evidence concerning how decision-making happens in real time. Objectives: Our objectives were as follows - create a data set of video- and audio-recordings of labour and birth in midwife-led units; use conversation analysis to explore how talk is used in shared decision-making; assess whether or not women's antenatal expectations are reflected in experiences and whether or not the interactional strategies used (particularly the extent to which decisions are shared) are associated with women's postnatal satisfaction; and disseminate findings to health-care practitioners and service users to inform policy on communication in clinical practice. Design: This was a mixed-methods study. The principal method was conversation analysis to explore the fine detail of interaction during decision-making. Derived from the conversation analysis, a coding frame was developed to quantify interactions, which were explored alongside questionnaire data concerning women's antenatal expectations and preferences, and women's experiences of, and postnatal satisfaction with, decision-making. Semistructured interviews with health-care practitioners explored factors shaping decision-making. Setting and participants: The study took place in midwife-led units at two English NHS trusts. A total of 154 women (aged ≥ 16 years with low-risk pregnancies), 158 birth partners and 121 health-care practitioners consented to be recorded. Of these participants, 37 women, 43 birth partners and 74 health-care practitioners were recorded. Key findings: Midwives initiate the majority of decisions in formats that do not invite women's participation (i.e. beyond consenting). The extent of optionality that midwives provide varies with the decision. Women have most involvement in decisions pertaining to pain relief and the third stage of labour. High levels of satisfaction are reported. There is no statistically significant relationship between midwives' use of different formats of decision-making and any measures of satisfaction. However, women's initiation of decisions, particularly relating to pain relief (e.g. making lots of requests), is associated with lower satisfaction. Limitations: Our data set is explored with a focus on decision initiation and responses, leaving other important aspects of care (e.g. midwives' and birth partners' interactional techniques to facilitate working with pain) underexplored, which might be implicated in decision-making. Despite efforts to recruit a diverse sample, ethnic minority women are under-represented. Conclusions: Policy initiatives emphasising patient involvement in decision-making are challenging to enact in practice. Our findings illustrate that women are afforded limited optionality in decision-making, and that midwives orient to guidelines/standard clinical practice in pursuing particular decisional outcomes. Nonetheless, the majority of women were satisfied with their experiences. However, when women needed to pursue decisions, particularly concerning pain relief, satisfaction is lower. Conversation analysis demonstrates that such 'women-initiated' decision-making occurs in the context of midwives' avoiding pharmacological methods of pain relief at particular stages of labour. Future research: We suggest that future research address the following - the barriers to inclusion of ethnic minority research participants, decision-making in obstetric units, systematic understanding of how pain relief decisions are pursued/resolved, conversation analysis of interactional elements beyond the specific decision-making context, interactional 'markers' of the emotional labour and inclusion of antenatal encounters. Trial registration: This trial is registered as ISRCTN16227678 and National Institute for Health and Care Research (NIHR) CRN Portfolio (CMPS):32505 and IRAS:211358. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 36. See the NIHR Journals Library website for further project information.